2017
DOI: 10.1002/hep.29246
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐coenzyme A carboxylase inhibition reduces de novo lipogenesis in overweight male subjects: A randomized, double‐blind, crossover study

Abstract: NDI‐010976, an allosteric inhibitor of acetyl‐coenzyme A carboxylases (ACC) ACC1 and ACC2, reduces hepatic de novo lipogenesis (DNL) and favorably affects steatosis, inflammation, and fibrosis in animal models of fatty liver disease. This study was a randomized, double‐blind, placebo‐controlled, crossover trial evaluating the pharmacodynamic effects of a single oral dose of NDI‐010976 on hepatic DNL in overweight and/or obese but otherwise healthy adult male subjects. Subjects were randomized to receive either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 29 publications
4
92
0
Order By: Relevance
“…Treated hepatocytes did not take up excess free fatty acids, and liver cells did not activate transcription factors involved in lipid synthesis to synthesize more TGs; the result would be expected to be reduced hepatocyte lipid accumulation [34]. Interestingly, we also found that ginkgolide B did not decrease TG levels in serum.…”
Section: Discussionmentioning
confidence: 52%
“…Treated hepatocytes did not take up excess free fatty acids, and liver cells did not activate transcription factors involved in lipid synthesis to synthesize more TGs; the result would be expected to be reduced hepatocyte lipid accumulation [34]. Interestingly, we also found that ginkgolide B did not decrease TG levels in serum.…”
Section: Discussionmentioning
confidence: 52%
“…

We have studied a series of human acetyl-CoA carboxylase (ACC) 1 and ACC2 proteins with deletions and/or Ser to Ala substitutions of the known phosphorylation sites. A number of inhibitors of human ACCs have been studied [10,[12][13][14][15][16][17][18][19]. Our results are consistent with AMPK phosphorylation of Ser 29 , Ser 80 , Ser 1,201 , and Ser 1,216 .

…”
supporting
confidence: 86%
“…Such key roles of ACCs in fatty acid metabolism make them potential drug target [1][2][3][4][5][6][7][8][9][10][11]. In vitro dephosphorylation/phosphorylation experiments reveal a substantial level of phosphorylation of human ACCs produced in insect cells.…”
mentioning
confidence: 99%
“…(11) In addition, a liverdirected allosteric inhibitor of ACC1 and ACC2 (GS-0976) has been shown to improve hepatic steatosis and markers of liver injury in patients with NASH and to reduce hepatic steatosis and dyslipidemia in rodent models of obesity. (12)(13)(14) Despite this, the effect of liver-directed ACC inhibition on hepatic mitochondrial oxidation, anaplerosis, and ketogenesis in vivo is unknown. Here, we performed a comprehensive set of metabolic flux analyses to assess these parameters in both chow-fed rats and rat models of diet-induced obesity (DIO).…”
Section: See Editorial On Page 2062mentioning
confidence: 99%